J.C. Christensen: Første skridt på vejen til konseilspræsident - Trock, Carl (Kirkehistoriske Samlinger, 2007)
J. C. Christensen was bom in 1856 as the eldest of a farmer’s 9 children. 11 years old he arrived at the home of an uncle giving him the possibility of going to school. A competent and knowledgeable teacher inspired J. C. to become a teacher himself and having been confirmed he was employed as an assistant teacher at the age of 16. Later on, in 1874-75, he frequented Grundtvig’s Højskole near Copenhagen, and during the following years (1875-77) he was trained as a teacher at a seminary in Jutland. Having taught a couple of years he was married to a farmer’s daughter from the place from which he came himself, forcing him to look for a new job, which he found in Eastern Jutland, near Horsens, and at which he stayed from 1882 to 1886. That year he moved to a new teaching post in Stadil, close to the west coast ofJutland. During the 1870’ies and 1880’ies J. C. had followed the political development in which J. B. S. Estrup (Prime Minister since 1875), bypassing the majority of the Lower Chamber (Folketinget) of the Parliament, had granted money to the defence, especially to the fortifications of Copenhagen. Estrup succeeded in dividing the opposition into three factions, one led by Frede Bojsen, another by the more radical Viggo Hørup, and the third by Chr. Berg, who was to become J. C.’s example. J.C. was elected chairman of the local council in Stadil, an appointment he had never had before. Approaching the Parliamentary election in 1890 he was asked to run as a candidat, a request he hesitantly accepted as he knew, that being elected it would pose certain dangers to his spiritual life. At the election of 1890 Berg’s group was almost doubled to 17 members and J.C. was one of the newly elected among a group of farmers and smallholders from Jutland. Berg controlled his group and at the end of the session he wanted to know, how the work in the different committees had turned out. J.C. answered that very little concrete work in the three committees of which he was a member had been done, but apart from this he had had several discussions with his party colleagues, the budget being one of them. At the election of 1890 a couple of Social Democrats were elected to the Lower Chamber of the Parliament, one of them, newspaper editor Harald Jensen, was elected in the country. In his speech at Constitution Day, the Minitser ofJustice, Nellemann, spoke of the dangers posed by nihilism and socialism and urged for cooperation among opponents. But not all followed suit. Bojsen, in his struggle against the government, proposed several social laws, which J.C. on his hand opposed. During the preparations for the parliamentary election in 1892, Berg was forced to convalesce during midsummer, and member of the Upper Chamber of the Parliament (Landstinget) Madsen Mygdal took over in touring western Jutland accompanied by J. C. Berg returned after two months of absence, but died a few months later, in November of 1891. At the election 1892 Bojsen benefited from a gain of seats while the groups headed by Berg and Hørup respectively each lost two members. Hørup was not even re-elected. During the session Bojsen renewed his proposal on wages to the clergy hoping to get properties attached to the vicarages parcelled out, but the Minister for Educational and Ecclesiastical affairs (Kultusminister), C. Goos, expressed his scruples. To the important financial committee, two new members from Berg’s group were elected: J. C. along with Anders Nielsen. During the 1893-94 parliamentary sessions Bojsen approached a compromise with the government. This process was accompanied by several proposals concerning the church. One of these was proposed by J. C. He hoped that the churches could be opened for instructions and sermonizing by clergy and as well as by lay with a view to get preaching removed from the meeting halls and back to the churches. Another proposal by J. C. concerned the tithe on which he argued that it should be replaced while Berntsen from the moderate wing of the party argued that it could be replaced. The session ended with accept by Bojsen of the government’s defence policy, much to the annoyance ofJ. C. A great part of the Bojsen-group, led by Sofus Høgsbro and Alberti, left him and, later, joined the group originally headed by Berg, thereby creating the Reformed Left. Høgsbro was elected chairman and J. C. secretary. In 1897, Høgsbro retired and J. C. took over. During the 1890’ies Copenhagen and the larger provincial towns across the country expanded, and in the new districts the lack of churches was felt. Although § 3 in the Constitution granted the state’s support of the Danish church (Folkekirken), this was not sufficient as it was difficult to get laws passed concerning the construction of new churches. Claiming that there were sufficient churches, the Social Democrats opposed the erection of new churches and the supporters of the party grew in numbers. A foundation with the bishop of Sjælland (H. V. Sthyr) in front was formed with the aim of collecting money to the establishment of minor parishes with small churches. The foundation succeeded inbuilding new churches and in paying the clergy employed there.. While the Minister of Educational and Ecclesiastical Affairs regarded the development with some concern and the Social Democrats criticised the »begging« across the country solely for the purpose of building churches in the capital, J. C. supported the initiative. In 1897 he had questioned bishop Sthyr about his intensions. In the opinion ofJ. C. the future did not look bright if the clergy alone should reign the church. Those who carried its burdens and enjoyed its advantages were those who should be given the responsibilities. In the Parliamentary elections in 1895 and in 1901 the Right (Højre) had lost voters continually while the Left (Venstre) had gained further seats. J. C. had put forward a proposal in 1900 concerning the establishment of church councils in each parish in an attempt of extending the responsibility for the church by including the laity as well. The proposal was opposed by the minister responsible and was voted down by the Upper Chamber of the Parliament. The result of the election in 1901 made the king, Christian IX, real- ise, that the time had come to let the Left form the new government, in which J. C. became Minister of Educational and Ecclesiastical Affairs, and thereby paving the way for much needed reform of the Church.